A Set Of Early Iron Age Discovered at Dhat Khayl Near Al-Hamra (Ad-Dakhiliyah), Oman - Gernez, Guillaume (The Journal of Oman Studies, 2025)
A set of objects, mainly made of copper/bronze, was discovered fortuitously during development work at Dhat Khayl, a village in the wilayat of al-Hamra (ad-Dakhiliyah) located at the foot of the mountains of central Oman. These vessels, daggers and bangles are all typical of the Early Iron Age and correspond to well-known types from this period. Although the context is not documented, it is likely that these objects were originally part of a funerary assemblage. The quality and homogeneity of the material is remarkable, allowing it to be accurately dated and placed in the cultural context of its production and distribution.